REPRESENTASI SPIRIT HYANG PERTIWI DALAM TARI LEGONG KREASI MAHA WIDYA - Ni Komang Ayu Dita Lestari; Ni Nyoman Manik Suryani; I Wayan Sutirtha (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2023)
The Legong Kreasi Maha Widya is a dance perfomed by five female dancers, inspired by the power or stronger of Mother Earth. The Maha Widya Kreasi Legong Dance was created by Anak Agung Mas Sudarningsih S.Sn., M.Pd who is a one of the active artists at the Pancer Langit Art Studio. Merdeka Learning program, studying Merdeka campus which is located at the Pancer Langiit Art Studio, students carry out research using descriptive analytical methods using a qualitative approach, which refers to the layout creative process and of performance through the Spirit Hyang Pertiwi contained in Maha Widya's Legong Dance. The results of data analysis show that the essence of the Representation of Spirit Hyang Pertiwi by Maha Widya's Legong Kreasi dance is not explained, but is otomatic presented with dramatic using a symbolic presentation mode.Oriented from this thought, The legong kreasi maha widya Dance was created using the principles of the Langon method sourced from Lontar Purwadigama which mention that there are concepts. three concepts such as (1) the concept of controller called is Ungon, (2) the concept of reinforcement called is Ingon, (3 ) the concept of mastery which is called Angon.Layout of Kreasi maha widya dance of Legong Dance consists of four structures consisting of we called Pepeson, Pengawak, Pengecet and pekaad.The purpose of the research Legong Kreasi Maha Widya dance is introduce to the public, for the position of Maha Widya's Legong Kreasi dance is inseparable from an innovation and creative idea that is owned as a inspiration artist to transform his ideas inspired by Nature which is a source of knowledge and strength for the universe, everything will certainly return to where we stand, namely Mother Earth. Key words : Mother Earth, Creative Process, The Legong Kreasi Maha Widya